Achieving value for money through procurement. Part 2: DFID’s approach to value for money through tendering and contract management - A perf ormance review - ICAI (Independent Commission for Aid Impact (ICAI), 2018)
Summary In 2016-17, the Department for International Development (DFID ) spent £1.4 billion, or 14% of its budget, through commercial supplie rs on contracts ranging from school construction to family planning se rvices and the delivery of humanitarian aid. The quality of its procur ement and contract management – how it engages and manages commercial firms to support the delivery of aid programmes on time, to budget and at the appropriate quality – is a key driver of value for money for U K aid. It is also a subject of considerable Parliamentary and public i nterest. In recent years, DFID has implemented a range of initiatives to strengthen its procurement practices and embed commercial capabilit y across the department – including its 2017 Supplier Review, undertak en to address concerns about excessive profit-making by DFID suppliers . This review on achieving value for money through procurement (part 2 ) was published in September 2018. We awarded a green-amber score and made three recommendations to government. The follow-up to this review was published in July 2020, and rated the government’s response as ‘i nadequate’, as a result of DFID’s failure to put in place a formal con tract management regime, despite the risks this entails for programme results. We will return to this in the next follow-up in summer 2021. Review Our review found an appropriate overall approach to procurement with good performance in most areas of tendering, but significant wea knesses in contract management. We therefore awarded a green-amber sco re and made three recommendations to government. Findings Since 2015, DFID has progressed towards a more mature procurement approach. DFID’s tender process follows current EU legislation and UK government guide lines and cross-government peer reviews confirm improvements in DFID’s procurement approach. The Supplier Review lent momentum to the reform s but risks having unintended consequences. Poor consultation with sup pliers has heightened the risk of unintended consequences. DFID is rev iewing its business processes to protect aid recipients from sexual ab use and exploitation. DFID does not always choose the most appropriate procurement process but a new strategic sourcing process has resulted in stronger procurement planning. DFID has built up its commercial ca pability, but this will need to be an ongoing process. The contract ma nagement function in DFID is poorly defined and contracts are frequent ly amended or extended beyond their advertised length and values. Ince ption phases are often too short for adequate preparation and planning . Progress on flexible and adaptive programming will require more inno vative approaches to tendering and contract management. Recommendation s Before the next major revision of its supplier code and contracting terms, or future changes that may materially affect suppliers, DFID sh ould conduct an effective consultation process with its supplier marke t, to ensure informed decisions and minimise the risks of unintended c onsequences. DFID should accelerate its timetable for acquiring a suit able management information system for procurement, to ensure that its commercial decisions are informed by data. DFID should instigate a fo rmal contract management regime, underpinned by appropriate training a nd guidance and supported by a senior official responsible for contrac t management across the department. The new regime should include appr opriate adaptive contract management techniques, to ensure that suppli er accountability is balanced with the need for innovation and adaptiv e management in pursuit of development results.